2018
DOI: 10.1002/ejlt.201700441
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, In Vitro Digestibility and Stability of Flaxseed Oil and Quercetin Co‐Loaded Submicron Emulsions

Abstract: Flaxseed oil and quercetin have received extensive attention in food industry. However, their poor solubility in water and stability are major limitations for their application in functional foods. In this work, we encapsulated flaxseed oil and quercetin into submicron emulsions by high pressure homogenization method to overcome their shortcomings in application. The loading of flaxseed oil in submicron emulsions was 10% and the solubility of quercetin in water is increased by at least 1300 folds. In vitro ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The lipolysis products (free fatty acids, surfactants, and dissolved bioactive substances), bile salts, and phospholipids assemble into mixed micelles and vesicles, then they are transported to the intestinal tract for absorption. [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…The lipolysis products (free fatty acids, surfactants, and dissolved bioactive substances), bile salts, and phospholipids assemble into mixed micelles and vesicles, then they are transported to the intestinal tract for absorption. [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of QU-SE is much greater than FO-SE, whereas QU-FO-SE (>90%) showed a synergistic effect in the antioxidant capacity. [62] Figure 9G,H displays the comparison of H 2 O 2 scavenging activity among pure QU, optimized QU-loaded MLs (OF 1 -OF 3 ), and QLPs (L 1 -L 3 ) at different concentrations. The H 2 O 2 assay revealed an increasing antioxidant profile for QMLs, QLPs, and QU with increasing concentration from 66.66 to 266.64 µg mL −1 .…”
Section: Antioxidant Activity: In Vitro Radical Scavenging Assaysmentioning
confidence: 99%
“…The past studies reported that adequate consumption of ω‐3 PUFAs is responsible for preventing cardiovascular and inflammatory diseases, as well as improving brain function (Lordan et al ., 2020). Consequently, there is an increasing trend of using ω‐3 PUFAs‐based emulsions for delivering bioactive (Sharif et al ., 2017; Huang et al ., 2018). In a study, Walia et al .…”
Section: Introductionmentioning
confidence: 99%